A Cross-National Comparative Study on Factors Influencing User Entrepreneurial Intention: A Perspective from Institutional Theory - Zhou, Jinbo; Cen, Weiren (Journal of Theory and Practice of Management Science, 2023)
This cross-national comparative study examines the factors influencing user entrepreneurial intention in the United States, Germany, and China from an institutional theory perspective. The research aims to fill the existing gap in understanding the determinants of entrepreneurial intention, especially across different countries. The findings reveal that access to resources and support networks consistently impact user entrepreneurial intention in all three countries, underscoring the importance of providing aspiring entrepreneurs with essential resources and mentorship. Furthermore, the regulatory environment significantly influences user entrepreneurial intention, particularly in Germany, where supportive government policies and business regulations play a crucial role. Cultural values also play a significant role in China, where societal attitudes towards entrepreneurship and innovation shape entrepreneurial intention. These findings emphasize the importance of considering institutional factors and cultural norms when formulating policies and initiatives to foster a conducive environment for user entrepreneurship.